Comparison of the procedure results of ectopic papillae encountered during ERCP procedure with the procedure results of papillae with normal localization - Ballı, Emre; Akay, Tamer; Yılmaz, Sezgin (Journal of Surgery and Medicine, 2021)
Background/Aim: In Endoscopic retrograde cholangiopancreatography (ERCP), Ampulla of Vater is found on the posteromedial wall of the second part of the duodenum. However, ectopic expansion of the common bile duct to the 3rd or 4th part of the duodenum or the proximal stomach, pylorus, or bulb was reported in the literature. This study primarily aims to investigate the risk of complications in patients with ectopic papillae and evaluate the applicability of endoscopic sphincterotomy in these patients. Methods: In this a case-control study, the data of 3,048 patients who underwent ERCP procedure in the ERCP unit of our clinic between January 2013 and December 2018 were retrospectively analyzed, and 30 patients with ectopic bulbar papillae and 30 randomly selected patients with normally localized papillae were compared in terms of age, gender, duration of the procedure, post-procedural biochemical tests, cannulation success, precision rate, postprocedural pancreatitis complications and the need for analgesics. Power analysis was performed with the G*power 3.1.9.7 package program (1-B = 0.95, alpha = 0.05). With a power of 0.954, the sample size to be reached was thirty-three for each group. Results: The rate of pancreatitis complications was higher in patients with ectopic bulbar papillae (50%) compared to those without (16.7%) (P=0.006). Even though the rate of pre-cut was higher in patients with ectopic bulbar papillae (33.3%) compared to patients with normally localized papillae (13.3%), this difference was not statistically significant (P=0.063). Cannulation success in patients with ectopic bulbar papillae (83.3%) was insignificantly lower than in patients with normally localized papillae (90.0%) (P=0.353). The need for both narcotic and non-steroidal anti-inflammatory analgesics was higher in patients with ectopic bulbar papillae (P<0.001, P=0.005, respectively). Conclusions: It should be kept in mind that ectopic biliary drainage may be found in an alternative location when no papillae are observed in the expected anatomical region. The complication risks, including pancreatitis, are increased in the intervention of ectopic papillae. Novel studies showing that endoscopic sphincterotomy and pre-cut are successfully used in patients with ectopic papillae are needed.